Socrates in the schools from Scotland to Texas: Replicating a study on the effects of a Philosophy for Children program. (2015) - Fair, Frank; Haas, Lory E; Gardosik, Carol; Johnson, Daphne D; Price, Debra P; Leipnik, Olena
No abstract available